An internet-delivered handwashing intervention to modify influenza-like illness and respiratory infection transmission (PRIMIT): a primary care randomised trial. Issue 10004 (24th October 2015) - Little, Paul; Stuart, Beth; Hobbs, F D R; Moore, Mike; Barnett, Jane; Popoola, Deborah; Middleton, Karen; Kelly, Joanne; Mullee, Mark; Raftery, James; Yao, Guiqing; Carman, William; et al.
Summary: Background: Handwashing to prevent transmission of respiratory tract infections (RTIs) has been widely advocated, especially during the H1N1 pandemic. However, the role of handwashing is debated, and no good randomised evidence exists among adults in non-deprived settings. We aimed to assess whether an internet-delivered intervention to modify handwashing would reduce the number of RTIs among adults and their household members. Methods: We recruited individuals sharing a household by mailed invitation through general practices in England. After consent, participants were randomised online by an automated computer-generated random number programme to receive either no access or access to a bespoke automated web-based intervention that maximised handwashing intention, monitored handwashing behaviour, provided tailored feedback, reinforced helpful attitudes and norms, and addressed negative beliefs. We enrolled participants into an additional cohort (randomised to receive intervention or no intervention) to assess whether the baseline questionnaire on handwashing would affect handwashing behaviour. Participants were not masked to intervention allocation, but statistical analysis commands were constructed masked to group. The primary outcome was number of episodes of RTIs in index participants in a modified intention-to-treat population of randomly assigned participants who completed follow-up at 16 weeks. This trial is registered with the ISRCTN registry, number ISRCTN75058295. Findings: Across three winters between Jan 17, 2011, and March 31, 2013, we enrolled 20 066 participants and randomly assigned them to receive intervention (n=10 040) or no intervention (n=10 026). 16 908 (84%) participants were followed up with the 16 week questionnaire (8241 index participants in intervention group and 8667 in control group). After 16 weeks, 4242 individuals (51%) in the intervention group reported one or more episodes of RTI compared with 5135 (59%) in the control group (multivariate risk ratio 0·86, 95% CI 0·83–0·89; p<0·0001). The intervention reduced transmission of RTIs (reported within 1 week of another household member) both to and from the index person. We noted a slight increase in minor self-reported skin irritation (231 [4%] of 5429 in intervention group vs 79 [1%] of 6087 in control group) and no reported serious adverse events. Interpretation: In non-pandemic years, an effective internet intervention designed to increase handwashing could have an important effect in reduction of infection transmission. In view of the heightened concern during a pandemic and the likely role of the internet in access to advice, the intervention also has potential for effective implementation during a pandemic. Funding: Medical Research Council.